Atividade biológica de óleo essencial de Cymbopogon winterianus e Thymus vulgaris em isolados clínicos de Cryptococcus neoformans - Nunes, Reginaldo Teixeira (2014)
The basidiomycete Cryptococcus neoformans is a pathogenic yeast responsible for causing meningoencephalitis in patients with a compromised immune system, leading to high mortality rates worldwide. Presently available antifungal drugs for treating this disease are not always efficient and they may lead to serious side effects and sometimes to fungal resistance. This situation has caused an increasing search for natural products derived from plants with antifungal action. Cymbopogon winterianus Jowitt (Poaceae), popularly known as citronella and Thymus vulgaris L. (Labiatae), known as thyme, are two plants commonly used in folk medicine. This study aimed at evaluating the biological activity of both C. winterianus and T. vulgaris essential oils (EOs) on C. neoformans clinical isolates. We evaluated the in vitro susceptibility of C. neoformans to each EO by the broth microdilution method, the in vitro interaction between EOs and fluconazole by the checkerboard method, their toxicity on human erythrocytes and their effects on the mitochondrial metabolism of fungal cells. Both EOs showed to possess antifungal activity against the tested isolates, with minimum inhibitory concentrations (MICs) ranging from 32 to 256 μg/mL for C. winterianus and from 32 to 128 μg/mL for T. vulgaris. No synergism between the EOs and fluconazole was observed. C. winterianus and T. vulgaris EOs did not cause hemolysis on human erythrocytes at concentrations corresponding to MIC values, indicating, therefore, low toxicity. The MTT assays showed no alterations on mitochondrial metabolism of fungal cells by C. winterianus at concentrations ≤ 128μg/mL, as well as no alterations at any concentrations corresponding to MIC values by T. vulgaris, suggesting that the main mechanism of action of both EOs is not by interfering with mitochondrial activity. Results show that C. winterianus and T. vulgaris EOs may be promising on the production of new antifungal drugs.